Applications of Heritage Building Information Modeling (HBIM) : A bibliometric review and future trends - Baarimah, Abdullah O.; Idrissi Gartoumi, Khalil; Alaloul, Wesam Salah; Liew, Mohd Shahir; Alawag, Aawag Mohsen; Ba Hamid, Rami Abdullah Ali (Institute of Electrical and Electronics Engineers Inc., 2023)
Building Information Modeling (BIM) has become the top of the agenda in the fields of Architecture, Engineering and Construction (AEC). This technology has contributed throughout the entire life cycle of construction, including the operations management phase. Under the umbrella of the BIM Legacy, the BIM approach has been able to expand to manage existing and legacy buildings. Recently, Heritage Building Information Modeling (HBIM) may have a significant potential to support the management, conservation, design, and maintenance of heritage as a consolidated technique for heritage preservation. HBIM has been prominent in several previous studies. However, there is a lack of studies that summarise the disciplinary fields that have been addressed previously. The study's aim is to perform a scientometric analysis of the existing HBIM scientific literature and to provide a picture of the research status from 2018 to March 2023. There were 248 articles extracted from the Scopus database. 'VOSviewer' tool was employed to visualize the literature containing the most active scientific journals, countries, and highly used keywords. Furthermore, the recent studies on the impact of HBIM and its applications in the heritage field are reviewed. Accordingly, this paper provides a valuable reference for researchers to focus on potential areas related to HBIM.